Fluorescence guided versus conventional surgical resection of high grade glioma : a single centre 7 year comparative effectiveness study - Ping, Ng Wei (2016)
Background High grade gliomas (HGGs) are locally invasive and aggressive brain tumors that carry dismal prognosis. Despite the rapidly evolving therapeutic strategies to treat HGGs, Malaysia still failed to demonstrate the expected standard HGGs management. According to National Comprehensive Cancer Network (NCCN) Guideline, the current standard management of HGGs includes maximum safe microsurgery resection followed by chemotherapy and radiotherapy. Complete resection, though increases median survival, is often hindered by the challenge of demonstrating the tumor border reliably. Department of Neurosurgery Hospital Sungai Buloh therefore has adopted fluorescence guided (FG) surgery using 5-aminolevulinic acid (5-ALA) as the first public hospital in Malaysia to overcome this shortcoming since 2010.